Characterization of oxide layers formed on 10CrMo9-10 steel operated for a long time in the power industry - Gwoździk, Monika; Ullrich, Christiane; Schimpf, Christian; Rafaja, David; Kulesza, Sławomir; Bramowicz, Mirosław (Bulletin of the Polish Academy of Sciences. Technical sciences, 2021)
This paper presents the results of diagnostic examinations conducted on the coils of super-heaters made of 10CrMo9‒10 steel that were operated in industrial conditions at 480°C for 130 thousand hours. The tube was exposed in a coal-fired boiler. The chemical and phase composition of the oxide/deposit layers formed on both sides of the tube walls (outside – flue-gas side and inside – steam side) and their sequence was examined using optical microscopy, scanning electron microscopy with electron backscatter diffraction and energy-dispersive X-ray spectroscopy, and X-ray diffraction. The changes in the mechanical properties caused by corrosion and aging processes were concluded from the hardness measurements. In addition, the nature of cracks in the oxide layers caused by pressing a Vickers indenter was determined. The results of these examinations have shown a high degradation of steel on the flue-gas inflow side and identified the main corrosion products and mechanisms.